ISLAMIC BANKING PERFORMANCE BASED ON BANK HEALTH BEFORE AND DURING THE COVID-19 - Lestari, Suryani Sri; Hasanah, Siti; Widodo, Saniman; Widowati, Mustika; Katrinasari, Mella (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The research entitled